Lichens from the area drained by the Peel and Mackenzie rivers, Yukon and Northwest Territories, Canada. II. Microlichens - Bird, Charles D.; Thomson, John W.; Marsh, Alfred H.; Scotter, George W.; Wong, Pak Yau (Canadian Journal of Botany, 1981)
A sequel to earlier papers on bryophytes and macrolichens, this treatment describes the distribution and general ecology of 314 microlichen taxa for 230 000 km 2 of coniferous forest, open fens, and alpine terrain along the Mackenzie River in the District of Mackenzie, Northwest Territories, and the Peel River, a major tributary which extends into the Yukon Territory. There are 103 new reports for the District of Mackenzie and 69 for the Yukon. Of the taxa, 87% are found in Europe and Asia as well as in North America, 1% are known only from Asia and North America; and 9% are restricted to North America. Staurothele sessilis Magn. is new to Canada, while Sagiolechia protuberans (Ach.) Mass., Staurothele hymenogonia (Nyl.) Th.Fr., and two lichen parasites, Didymosphaeria epicrassa (Oliv.) Vouax and Lahmia fuistingii Körb. are new to North America.Seven new combinations are made in Aspicilia: A. aliena (Zahlbr.) Thoms., A. anseris (Lynge) Thoms., A. elevata (Lynge) Thoms., A. perradiata (Nyl.) Thoms., A. ryrkaipiae (Magn.) Thoms., A. sorediza (Lynge) Thoms., and A. subplicigera (Magn.) Thoms.